Embracing diversity in Islam - Aung, Maulana Akbar Shah @ (2020)
Tolerance: the ability or willingness to tolerate the existence of opinions or behaviour that one dislikes or disagrees with. the capacity to endure continued subjection to something such as a drug or environmental conditions without adverse reaction. Race: relating to race. on the grounds of or connected with difference in race. Prejudice comes from the words 'to judge before'. It is forming an unfavourable opinion or feeling about a person or a group of people, without a full examination of the situation. In theory, it is possible for somebody to be prejudiced without anybody else knowing about it. What is discrimination? Discrimination is making a distinction against a person or thing based on the group, class or category they belong to, rather than basing any action on individual merit.